Internalisasi Nilai-Nilai Pendidikan Agama Islam Dalam Membentuk Karakter Siswa Melalui Budaya Religius - Destatil Maghfiroh; Nur Aisyah (CV Edujavare Publishing, 2023)
his study aims to describe the strategy of teachers internalizing the values of Islamic religious education in shaping student character through religious cultural construction carried out at SDN Cermee 1 Bondowoso and MI Darul Falah Cermee Bondowoso to shape religious character in students. The research method used is a qualitative research approach with a type of case study research. Data collection techniques through observation, interviews, and documentation. The data were analyzed using data reduction, data presentation, and inference. From the results of the research that has been done, it can be concluded that the internalization of Islamic religious education values in shaping student character through religious culture, namely: teacher strategies in internalizing Islamic religious education values to form character have three stages, First, the transformation of values through the values of aqidah, morals, worship, and society, the second value transaction is through the values of aqidah, morals, worship, and society Third, transinternalization through the values of aqidah, morals, worship, and society.